EXPLORING THE CONNECTION AMONG LANGUAGE, CULTURE, IDENTITY AND DIFFERENCE - Dodi Widia Nanda (STKIP Siliwangi, 2021)
This paper aims to explore the link among language, culture, identity and difference. It is beneficial to analyse because it contributes on the development of language education. The reason is that language learning and culture are inherent each other. This research’s method is the reflective inquiry as the part of qualitative research. This study scrutinises writer’s personal experiences concerning the link among language, culture, identity and difference. Hence, the research’s subject in this research is the writer’s personal experiences. Specifically, the writer’s experiences are intonation in expressing angriness and interacting with Jakarta people. The related experiences are written and collected by taking notes, and it is directly analysed when the data collected. The study’s result indicates that there has been a robust connection among language, culture, identity and difference. One’s culture and language can signify their identity and difference. Therefore, the connection between language, culture, identity and difference is required to explore in order to elicit significant impact on the development of language learning. Keywords: Language, Culture, Identity, Difference, Language learning